Ribosomal protein S6 is hyperactivated and differentially phosphorylated in epidermal lesions of patients with psoriasis and atopic dermatitis. (1st December 2014) - Ruf, M.T.; Andreoli, A.; Itin, P.; Pluschke, G.; Schmid, P.
Summary: Background: The ribosomal protein S6 is part of the translation machinery and is activated by phosphorylation via the mammalian target of rapamycin pathway, which is activated in psoriatic skin. Objectives: To investigate which S6 sites are phosphorylated in psoriasis and atopic dermatitis (AD), and to study whether S6 phosphorylation is associated with inflammation and/or keratinocyte hyperproliferation. Methods: Healthy skin and skin lesions of patients with psoriasis and AD were investigated by immunostaining using antibodies that stain proliferating cells, leucocytes and distinct phosphorylated sites of S6. Results: All psoriasis and AD lesions revealed abnormal S6 phosphorylation in the epidermis. The extent of S6 phosphorylation was diverse, generally stronger in psoriasis and correlated, in both diseases, with inflammation. S6 showed differential phosphorylation in distinct epidermal layers, which was most pronounced in hyperproliferative regions. Conclusions: Differential S6 phosphorylation may have a role in abnormal keratinocyte proliferation/differentiation.